DEVELOPMENT OF CREATIVE ACTIVITIES THROUGH BATIK DECORATIVE ART VARIETY TO IMPROVE KINDERGARTEN TEACHERS' CREATIVITY - Novysa Basri; Rudy Juli Saputra; Fauziatul Halim; Alfi Syahrin (JURNAL PAJAR (Pendidikan dan Pengajaran), 2023)
This paper reviews the development of Al-Muna Kindergarten teachers’ activities to improve the teachers’ creativity through Batik decorative designs. The research method uses qualitative methods with an interdisciplinary approach. The research data were collected by observation, interview, and documentation techniques. Checking the data validity uses source triangulation. Subsequently, it is analyzed through flow reduction, presentation, and data verification. The results indicate that the development of Batik’s decorative design of creative activities had an impact on the improvement of teachers’ ability in the art of creativity. Through Batik’s decorative designs, the teacher's creativity was formed by definition, namely the formation of one's personality with a positive side to find out new things by creating prases (systems) and products. The product produced is the making of Batik motif paintings with decorative designs on glass media, where the activity development period is for two weeks with two activity stages. Al-Muna Kindergarten teachers’ involvement was 10 teachers with a basic understanding of art that has almost the same assumption survey, which states that teacher's creativity art has not developed yet as expected in terms of professional competency development for PAUD teachers with cheerful and flexible principles. Thus, the research results indicate a good impact on Al-Muna Kindergarten teachers’ development.